Impact of long term policies based on social determinants of health: the Costa Rican experience - Morice Trejos, Ana (2011)
The consolidation of Democracy and the abolition of the army in Costa Rica at the end of the 1950s, instituted in the Political Constitution, led to the decision to prioritize the investment of public resources in the social sector as a strategy to advance towards the development of the country. The creation of a solid legal framework, the absence of a rigid stratification connected to a hierarchy of power that generates different access to resources, the implementation of democratic elections with high participation, and the development of public infrastructure have been essential factors in assuring access to education, access to water and basic sanitation as well as to access to health, and social security. Between 1950 and 1980, Costa Rica increased public social spending from 8.6% to 23.6% of the GDP, demonstrating the political will to invest in social determinants, in order to universalize access to education, safe water for consumption, basic sanitation, and primary health care. During this period the illiteracy rate was reduced from 21% to 10%, the average number of years of study increased and the level of education of the economically active population improved. Access to drinking water increased from 53% to 86% and coverage of the population’s health services and social security increased from 8 to 75%. Poverty, measured by level home income, declined from 50% in 1960 to 25% at the beginning of the 1980s. The decline in infant mortality during the period 1960-1980 showed that the least the educational level of mothers, the greater the increase in the probability of surviving, showing a positive effect of public policies and access to education in most secluded populations. At the national level, between 1970 and 1980 infant mortality was reduced from 68.4 to 18.1 x 1000 live births achieving a rate of 9.2 in 2010. Fertility declined from 4.8 to 1.8 and life expectancy increased from 65.8 to 79.2 years, reaching a total of 81.9 years in women in 2010. At the end of the 1980s in the middle of a global economic crisis, Costa Rica implemented a Health Sector Reform process that led to the adaptation of a model of care and delivery of services under the Costa Rican Social Security Fund, strengthening the leading role of the Ministry of Health as a guarantorfor the well-being of the population. The key strategy has been to advance toward health promotion by addressing its determinants to reduce the social gaps. The case of Costa Rica demonstrates that sustained public investment in the social sector with a long term vision has generated a redistributive effect of resources through interventions targeted to address the social determinants. The increase in the educational status and participation of women in the work force and in the political area has been a determinant associated with the improvement of the health indicators. Monitoring and evaluating, transparency, accountability and management, are key factors that have facilitated greater social development.